All Days 2015
DOI: 10.4043/25839-ms
|View full text |Cite
|
Sign up to set email alerts
|

Steel Catenary Risers (SCRs): From Design to Installation of the First Reeled CRA Lined Pipes. Part I - Risers Design

Abstract: Steel catenary risers (SCR) have been a favored choice for recent ultra-deep waters field developments subjected to harsh environments and large floating production units (FPU) motions. The design of SCRs in such conditions is always a great challenge where the key issues are the fatigue near the hang-off and at the touch down point; clashing between lines, especially on fields with a large number of wells and high payloads on the production unit. This paper describes the solution provided by the Buoy Supporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Since this methodology was never done before, spooling trials were suggested by Subsea7, operator and partners in order to perform a full scale test to approve the methodology, Details of the mechanically lined pipe qualification for pressurized reeling are presented in (Gouveia, J., 2015). Four short stalks were fabricated for the trials, totaling approximately 600m in length, considering both bare C-Mn pipes and mechanically lined pipes.…”
Section: Spooling Of Mechanically Lined Pipesmentioning
confidence: 99%
“…Since this methodology was never done before, spooling trials were suggested by Subsea7, operator and partners in order to perform a full scale test to approve the methodology, Details of the mechanically lined pipe qualification for pressurized reeling are presented in (Gouveia, J., 2015). Four short stalks were fabricated for the trials, totaling approximately 600m in length, considering both bare C-Mn pipes and mechanically lined pipes.…”
Section: Spooling Of Mechanically Lined Pipesmentioning
confidence: 99%
“…The riser system can be designed for pipeline class welds, e.g., F1 class; hence exotic material such as mechanically lined clad pipe (BuBi pipe, as used for the BSR system [10]) can be used for the SCR part. Since the platform motions are un-coupled in this riser system, the fatigue in the SCR part is very small.…”
Section: Catenary Offset Buoyant Riser Assembly (Cobra)mentioning
confidence: 99%
“…For a detailed description, please refer to (Gouveia, J., et al, 2015). The following bullets summarize the most important assessments to fulfill the risers design scope.…”
Section: Otc-26332-msmentioning
confidence: 99%